Implementación de Terminales Ligeras para fomentar el uso tecnológico en los procesos de enseñanza aprendizaje en el Centro de Educación Básica Carlos Arturo Chata de la parroquia Guanujo del cantón Guaranda durante el año lectivo 2019 – 2020 - Gualpa Hidalgo, Ramiro Efraín (2020)
The technological proposal with the theme of: "Implementation of light terminals to promote technological use in the teaching-learning processes", was carried out at the "Carlos Arturo Chata" Basic Education Center, is located northeast of the Bolivar province, specifically in the Pucará community, which belongs to the urban parish of Guanujo, Guaranda canton, in the 2019-2020 school period. In order to comply with the proposal, the situational analysis of the institution and the requirements analysis of the proposed system were carried out first. Thus, the situational analysis, after direct observation, manages to identify the problem that they do not have sufficient computer equipment for the use of their students and the few computers that currently have many are in poor condition or obsolete, consequently There is a non-functional computer center, which is detrimental to developing classes using computer tools. In addition, most of the students are of limited economic resources, making it very difficult for them to access the daily use of this type of equipment. technological. To solve this problem, it is proposed to implement light terminals. Based on the Top Down network methodology, evaluation of this was the analysis of the requirements and architectural design of the network for light terminals carried out before the selection of specific components, so it is a logical design, which seams in establishing the star network topology and logical design that refers to a scheme project of the physical components in the space where the terminal system is implemented. The development phase itself is where the server and the light terminals are adapted, installed and configured, to subsequently carry out the pilot test that helps us to detect some problems and with the satisfaction survey that is done to the students the system is improved. In the end, the implementation of the light terminals left the authorities, teachers and students of the beneficiary institution very satisfied, both in their physical disposition, as in their configuration, which ensures that their useful life is relatively long, which It means that several generations of students can be beneficiaries with this laboratory.